ANALISIS PEMASARAN KEMENYAN (Styrax spp.) DI DESA SIMARIGUNG (STUDY KASUS DI DESA SIMARIGUNG, KEC. DOLOK SANGGUL, KAB. HUMBANG HASUNDUTAN - Sori B M Lumban Gaol; Defri Yoza; Tuti Arlita (Fakultas Pertanian, Universitas Riau, 2017)
The purpose of this research is to know margin, efficiency and profit so that it is known that marketing channel is the most profitable for the farmer and we can identify the problems faced by farmers and traders. The data colleted from farmers and traders of Simarigung Village, Village Office and BPS Humbang Hasundutan. The method used is a simple random sampling. From the research obtained that farmers and traders Simarigung Village has a cooperative relationship based on the principle of kinship, Patrilineal system on the tribe of Batak cause farmers and traders to deal with the closeness of kinship. The marketing channel of Simarigung Village is divided into 2 channels and a more profitable marketing channel for farmers is the second marketing channel. Marketing channel marketing margin I is Rp. 50.000,00 and marketing channel II Rp. 30.000,00 then efficiency of marketing channel I is 7,66% and marketing channel II is 7,33% then marketing profit of marketing channel I is Rp. 27.000,00 and marketing channel II is Rp. 8.000,00.